2017
DOI: 10.32674/jis.v7i2.378
|View full text |Cite
|
Sign up to set email alerts
|

Do Chinese International Students’ Personalities Change During Cross-National Transitions?

Abstract: Perfectionism is a multidimensional personality construct salient for international students; they are known to be likely high achievers in their home country and face several acculturative challenges after crossing national borders. This study examined whether perfectionist types changed during cross-national transitions in a sample of 227 Chinese international students studying in the U.S. Individuals were classified into different types of perfectionists—adaptive, maladaptive, and non- perfectionists. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Similar to Wang et al (2017) conclusions, we believed that Chinese international students are likely to experience this unhealthy form of perfectionism (i.e., maladaptive perfectionism) when encountering acculturative stress due to cultural values that encourage high standards and the difficulties to meet their high expectations. First, perfectionistic behaviors were found to stem from cultural emphases on work ethic and education (Yee, 1992).…”
Section: Maladaptive Perfectionism As a Mediatorsupporting
confidence: 68%
See 3 more Smart Citations
“…Similar to Wang et al (2017) conclusions, we believed that Chinese international students are likely to experience this unhealthy form of perfectionism (i.e., maladaptive perfectionism) when encountering acculturative stress due to cultural values that encourage high standards and the difficulties to meet their high expectations. First, perfectionistic behaviors were found to stem from cultural emphases on work ethic and education (Yee, 1992).…”
Section: Maladaptive Perfectionism As a Mediatorsupporting
confidence: 68%
“…Based on Berry (1997) theoretical framework of acculturation, the association between acculturative stress and its immediate adjustment outcomes (e.g., depression and anxiety) is often mediated by individuals’ strategies or resources to deal with their stress. It is likely that in the face of acculturative stress, Chinese international students may engage in maladaptive perfectionism as a coping strategy to aid in their adjustment and adaptation in the U.S. (Wang et al, 2017). The use of maladaptive perfectionism then might further positively associate with elevated depression and anxiety.…”
Section: Maladaptive Perfectionism As a Mediatormentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to their socialization process, where they were loaded with heavy and frequent requirements and experienced a decrease in intrinsic motivation. On the other hand, Wang et al ( 2017 ) found that “there were more non-perfectionist [Chinese international] students who became perfectionists after studying in the United States. than perfectionists who became non-perfectionists” (p. 239).…”
Section: Introductionmentioning
confidence: 99%